High Discretion Slack: Penentu Keberhasilan Kinerja Organisasi Badan Usaha Miliki Desa (Bumdesa) - Nafidah, Lina Nasehatun; Hidayati, Laelly Wahyu (Universitas Muhammadiyah Gresik, 2024)
This research focuses on high discretion slack in achieving good organizational performance in Village-Owned Enterprises (BUM Desa). The type of data used in this research is primary data obtained from interviews with informants. This research will be conducted with a descriptive qualitative approach with a single case study on BUM Desa in Jombang district. The results showed that in BUM Desa there are unbound resources in the form of cash, working capital that can be utilized by managers in improving BUM Desa performance. However, these resources are not directly able to determine the success of BUM Desa performance. These unbound resources require the ability of managers, in this case human resources, to utilize these resources. The results of this study also show the limited ability of human resources in the village to drive BUM Desa, in addition to the low level of community participation in assisting BUM Desa management makes BUM Desa difficult to develop, even though the resources owned are high. Thus, human resource capability and village community participation are important factors to be used as benchmarks in maximizing resource utilization for the successful performance of BUM Desa.